The Use of Peptide Receptor Radionuclide Therapy in Patients With Neuroendocrine Tumor Cardiac Metastases. (January 2021) - Yu, Irene S.; Funk, Gayle; Lin, Eugene; Kennecke, Hagen F.
Abstract : Abstract: Cardiac metastases are an infrequent site of metastasis in neuroendocrine tumors, and the treatment implications in the era of peptide receptor radionuclide therapy (PRRT) are unclear. Potential safety concerns exist regarding cardiac integrity and function in response to PRRT. We describe our institutional experience with 4 patients with well-differentiated, midgut neuroendocrine tumors with cardiac involvement detected on 68 Ga-DOTATATE PET/CT scans who were treated with PRRT.